2013
DOI: 10.5433/1679-0359.2013v34n6supl2p3859
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian follicular dynamics of Nelore (Bos indicus) cows subjected to a fixed-time artificial insemination protocol with injectable progesterone

Abstract: This study aims to evaluate ovarian follicular dynamics of Nelore cows subjected to fixed-time artificial insemination (FTAI) with injectable progesterone (P4) or intravaginal device. In the device group, 20 cows received an intravaginal device with 1 g P4 and administration of 2 mg estradiol benzoate (EB) intramuscularly (im) on D0. The device was removed on D8, followed by administration of 500 μg cloprostenol, 300 IU equine chorionic gonadotropin (eCG) and 1 mg estradiol cypionate (EC), im. The cows were in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 12 publications
1
7
0
2
Order By: Relevance
“…Some reproductive parameters remain critical for the fertility of females synchronized with P4 injectable, such as the ovulation and pregnancy rates, but it is valid to highlight important aspects of this pharmacological strategy for reproductive management in cattle. In the present and other studies ( Morotti et al ., 2013a ; Morotti et al ., 2013b ; Campos et al ., 2016a ), greater convenience in managing animal synchronization was observed using P4 injectable. Such benefits are due to the convenience of a parenteral application in addition to the hygienic and sanitary advantages of injectable solution compared to intravaginal devices.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Some reproductive parameters remain critical for the fertility of females synchronized with P4 injectable, such as the ovulation and pregnancy rates, but it is valid to highlight important aspects of this pharmacological strategy for reproductive management in cattle. In the present and other studies ( Morotti et al ., 2013a ; Morotti et al ., 2013b ; Campos et al ., 2016a ), greater convenience in managing animal synchronization was observed using P4 injectable. Such benefits are due to the convenience of a parenteral application in addition to the hygienic and sanitary advantages of injectable solution compared to intravaginal devices.…”
Section: Discussionsupporting
confidence: 79%
“…To assist reproductive biotechnology, several pharmacological strategies have been proposed ( Sales et al ., 2012 ; Campos et al ., 2013 ; Barreiros et al ., 2014 ; Torres et al ., 2014 ; Marques et al ., 2015 ; Pellegrino et al ., 2016 ) and progesterone (P4) has been the main exogenous hormonal basis for estrus synchronization in cattle; treatment can be performed through intravaginal devices ( Macmillan et al ., 1991 ; Macmillan and Peterson, 1993 ), ear implants ( Baruselli et al ., 2004 ; Sa Filho et al ., 2011), oral formulations ( Fike et al ., 1999 ) or injectable sources ( Morotti et al ., 2013a ; Morotti et al ., 2013b ; Campos et al ., 2016a ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diversos autores já atestaram que os protocolos de IATF baseados na administração de estradiol e P4 são altamente eficientes em vacas Bos indicus (SÁ FILHO et al, 2011b;SALES et al, 2012). Entretanto, os estudos e possíveis avanços no sentido de minimizar o serviço e reduzir os custos ainda são necessários para que se continue progredindo na biotecnologia reprodutiva (MOROTTI et al, 2013). Neste sentido, a aplicação de uma quantidade menor de P4 injetável associado ao implante de quarto uso aparece como alternativa para reduzir os custos da IATF em propriedades de bovinocultura, já que o implante iria ser descartado, mesmo contendo uma pequena quantidade de P4.…”
Section: Resultsunclassified
“…Despite these relative advantages, another study conducted by the same research group showed that cows synchronized with injectable P4 showed a lower pregnancy rate (27.0 %) than did those synchronized with an intravaginal device (45.5 %) (MOROTTI et al, 2013b). Although a few studies have been conducted using injectable P4, more knowledge of this strategy's pharmacological adjustments, changes in the management of animal, and/or synchronization protocols could improve fertility in cows when synchronized this way.…”
Section: Introductionmentioning
confidence: 99%